Soil microzoning for stable foundations of single-family homes in the Santa Rosa neighborhood of the Lircay-Huancavelica district - Camac, Enrique (2023)
The objective of this research work was to develop the Microzoning of soils for the stable foundation of single-family homes in the District of Lircay of the Department of Huancavelica. The type of research according to employment in this work was applied research; It was based on a descriptive level, of the physical and mechanical properties of the soil of the Santa Rosa neighborhood, resulting in the specification of a microzoning map, and the design of a more stable base for a 3-story single-family home. Knowing the results of the different tests carried out in the laboratory, the physical, mechanical characteristics and the admissible capacity of the soil of said place were known, with which it was zoned into 3 zones. Zone I an admissible capacity of 1kg/cm2. For zone II, an admissible capacity of 1.2 kg/cm2 was determined. And zone III has an admissible capacity of 1.57 kg/cm2. In the 3 zones, their zoning map was prepared. zone I, zone II, zone III, respectively, there are soils; (Well graded sand with little presence of fines); (Silty sand with presence of fines); (Gracious sand without any fines). Finally, an adequate and stable superficial foundation was proposed. Zone I the following footings, central (2x2x0.40), median (2.10x1.30x0.40) and a corner (1.60x1.60x0.40). For zone II the following central footings of (1.70x1.70x0.40), median of (1.80x1.20x0.40) and a corner of (1.50x1.50x0.40). And in zone III the following central footings of (1.50x1.50x0.40), median of (1.6x1x0.40) and a corner of (1.30x1.30x0.40)